Patient and carer experiences of clinical uncertainty and deterioration, in the face of limited reversibility: A comparative observational study of the AMBER care bundle. (October 2015) - Bristowe, Katherine; Carey, Irene; Hopper, Adrian; Shouls, Susanna; Prentice, Wendy; Caulkin, Ruth; Higginson, Irene J; Koffman, Jonathan
Background: Clinical uncertainty is emotionally challenging for patients and carers and creates additional pressures for those clinicians in acute hospitals. The AMBER care bundle was designed to improve care for patients identified as clinically unstable, deteriorating, with limited reversibility and at risk of dying in the next 1–2 months. Aim: To examine the experience of care supported by the AMBER care bundle compared to standard care in the context of clinical uncertainty, deterioration and limited reversibility. Design: A comparative observational mixed-methods study using semi-structured qualitative interviews and a followback survey. Setting/participants: Three large London acute tertiary National Health Service hospitals. Nineteen interviews with 23 patients and carers (10 supported by AMBER care bundle and 9 standard care). Surveys completed by next of kin of 95 deceased patients (59 AMBER care bundle and 36 standard care). Results: The AMBER care bundle was associated with increased frequency of discussions about prognosis between clinicians and patients ( χ 2 = 4.09, p = 0.04), higher awareness of their prognosis by patients ( χ 2 = 4.29, p = 0.04) and lower clarity in the information received about their condition ( χ 2 = 6.26, p = 0.04). Although the consistency and quality of communication were not different between the two groups, those supported by the AMBER care bundle described more unresolved concerns about caring for someone at home. Conclusion: Awareness of prognosis appears to be higher among patients supported by the AMBER care bundle, but in this small study this was not translated into higher quality communication, and information was judged less easy to understand. Adequately powered comparative evaluation is urgently needed.